Commodification of high heels against women's bodies on dancer Jathil Obyog in the Reog Ponorogo art show - Bayu Aji Suseno; Putri Prabu Utami (Masyarakat, Kebudayaan dan Politik, 2022)
The performing art of Reog Ponorogo is a cultural heritage of the people of East Java which continues to experience development and several changes and progress. This study aims to identify the practice of commodifying high heels to complement the clothing of female dancer Jathil Obyog in the Reog Ponorogo art show. This study uses a qualitative method with a phenomenological approach. The results of this study explain that the high heels of Jathil Obyog dancers have value in supporting the appearance so that the legs look level, as well as forming a sturdy and proportional body posture in protecting the feet of female dancers in outdoor performances. The high heel exchange rate on Jathil Obyog's dancer's clothing is to raise the social status to an economic aesthetic value, while the symbolic value of high heels is a marker of sexuality for the female dancer Jathil Obyog to convey aggressiveness and eroticism to the audience, especially men. The conclusion of this study shows that high-heeled shoes can increase the sexual attractiveness (female body) of Jathil Obyog dancers by using a combination of semi-transparent or see-through tops, as well as the use of short pants that will make the thighs and buttocks look slimmer.